Tinker tailor soldier spy [videorecording (DVD)] - Alfredson, Tomas, 1965-; Oldman, Gary; Burke, Kathy, 1965-; Cumberbatch, Benedict, 1976-; Firth, Colin, 1960-; Le Carré, John, 1931- (Universal Studios Home Entertainment, 2012)
At the height of the Cold War, a former agent for the British Secret Intelligence Service is called back to root out a Russian spy who has infiltrated the organization's highest levels.